Ernesto Laclau : el populismo y sus avatares - Daniel Gutiérrez Vera (Íconos)
En el presente artículo consigno algunas reflexiones que me ha despertado la lectura de la obra de Ernesto Laclau. En especial, encontré sumamente sugestiva su reconsideración del viejo tópico del populismo. A mi entender, Laclau no solamente ha dado con una nueva forma de considerar el tema, sino lo político tout court. Mi perspectiva de lectura y evaluación de las propuestas de Laclau se apoya en el psicoanálisis, que constituye para mí el horizonte de cualquier reconstrucción posible de las ciencias sociales. This article offers a number of reflections inspired by a reading of Ernesto Laclau’s works. I found particularly suggestive his reconsideration of the old topic of populism. As I understand it, Laclau has found a new way to approach not only this issue, but also politics tout court. My perspective on reading and evaluating Laclau’s proposals is based on psychoanalysis, which for me constitutes the horizon of all possible social science reconstructions.